A study on prevalence of risk factors for non-communicable diseases among allopathic doctors of Vijayawada city, Andhra Pradesh - K., Kiran Prakash; Anga, Venkata Suresh (International Journal Of Community Medicine And Public Health, 2019)
Background: Chronic non-communicable diseases (CNCDs) are the leading cause of death in the world. Accounting for around 60% of all deaths and 44% of premature deaths worldwide. The objective of the study was to assess the prevalence of risk factors for non-communicable diseases among allopathic doctors in Vijayawada. Methods: A cross-sectional survey was conducted on allopathic practicing doctors who were working in the various Hospitals, clinics, Nursing Homes within the corporation limits of Vijayawada city. Results: Out of the 720 study subjects, 498 doctors (69.2%) were males and 222 doctors (30.8%) were females. majority of the doctors 515 (71.5%) were with educational qualification of master degrees (MS/MD/MDS). Doctors in clinical specialty are more 565 (78.5%) compared with non-clinical 133 (18.4%) and dental 22 (3.1%). With regarding working sector, nearly one third of doctors were working in private sector 532 (73.9%). Conclusions: Because of more exposure to unhealthy life styles like smoking, alcohol, unhealthy dietary habits like high intake of salt, inadequate use of fruits and vegetables, oil fries and by leading a sedentary life and high risk factors like overweight/obesity, hypertension and diabetes a large number of the doctor’s population were at increased risk for chronic non-communicable diseases.